How the reflux treatment stabilizes the metastable structure of ZrO2 and improves the performance of Ni/ZrO2 catalyst for dry reforming of methane?. (15th July 2020) - Zhang, Meng; Zhang, Junfeng; Zhang, Xiaoping; Zhou, Zeling; Song, Faen; Zhang, Qingde; Tan, Yisheng; Han, Yizhuo
Graphical abstract: Highlights: Reflux improves the activity, stability and coke resistance of Ni/ZrO2 catalyst. Si and K are inevitably residual during the reflux process within basic solution. Reflux can promote Ni dispersion, enrich the porosity and strengthen the basicity. Residual Si and K ions stabilize metastable phase and affect acid-base properties. Metastable structure is somewhat destroyed under long-life or high temperature run. Abstract: Ni/ZrO2 catalyst has been widely investigated for dry reforming of methane (DRM), but it suffers from rapid deactivation due to nickel aggregation and carbon deposition under the harsh conditions. Herein, we introduce the post-treatment of reflux in Ni/ZrO2 catalyst prepared by the conventional co-precipitation method. The detailed characterization results demonstrate that the catalysts after reflux exhibit the metastable structure with enlarged specific surface area and abundant porosity, thereby highly dispersing the active Ni species. The residue of Si and K is inevitable during the reflux process under the basic solution and the residual amount increases with the extended reflux time and the raised solution pH value. The residual Si is undesirable to improve the acidity while the residual K is expected to enhance the desirable basicity. Therefore, the stabilized metastable structure and mediated properties should be considered comprehensively in practically designing the highly active and stable DRM catalyst. The evaluation at 700 °C with gas hourly space velocity of 50000 mL·g −1 ·h −1 (volume ratio: CH4 /CO2 = 1/1) and time on stream of 600 min demonstrates that the treatment of reflux remarkably improves the activity and stability of Ni/ZrO2 catalyst. Especially, the catalyst with 5-day reflux displays the robust activity (CH4 conversion: 72%, CO2 conversion: 80%) and carbon-resistant ability (0.01 mg/mg cat.). However, although the metastable structure is somewhat stabilized by the treatment of reflux and the residual ions, eventually it is easily destroyed when suffering from long-life (6000 min) or high-temperature (beyond 800 °C) run, behaving as the sintering of Ni particles and carbon deposition.